Product Quality Control Using the Six Sigma method and Seven Tools in the PDL Shoe Industry - Siti Fatimah; Hana Catur Wahyuni (UNIPA PRESS, 2023)
CV Yunanda is one of the companies whose manufacturing process is in the form of shoes and sandals, CV Yunanda has one of PDL's main products in the field of leather footwear. The problem with this company is a production defect. Based on these problems, the purpose of this study is to determine the extent of the defects, determine the underlying causes of defective products, and make recommendations for improvement to reduce the number of defective products. This study uses seven tools and six sigma methods to identify the key factors that cause defective products and identify corrective actions to be taken based on the underlying factors. The results showed that there were 4 types of product defects, namely 13% overlapping skin defects and 11% flexed skin, 10% wrinkled skin, 7% scratched skin. The proposed solution is to control, inspect and perform maintenance on machines or equipment used in the production process, establish SOPs for each machine area, improve human resources through training and improvement of the work environment. Keywords Defect , Quality,